"They're Killing our Imaginations": Dialogue and Reflexive Writing Development in Historically Marginalized Students. Issue 3 (30th October 2021) - Spence, Lucy K.; Costa, Priscila J.B.M.; Cullars, Amanda
Abstract: Writing and identity development are enhanced when students have opportunities to discuss and write about their lives and concerns. This qualitative study explored sites of possibility for reflective, dialogic pedagogy within middle and high school writing instruction. The context for the study were three rural school districts that were test‐focused, historically marginalized, and majority African American. We collected classroom observations, student and teacher interviews, and writing samples over one academic year, and used writing identity and reflexivity to understand how students engaged in reflexive writing. Reflexivity involves reflecting on interests, values, beliefs, and power in relation to ideas or purposes. Our results indicate that dialogue and writing about meaningful topics contributed to a reflexive writing cycle. Within this cycle, dialogue was central to reflection and writing decisions. Conversely, limited opportunities to reflect and engage in dialogue resulted in fewer instances of reflexivity in the writing samples.